2021
DOI: 10.3390/medicina57121388
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rates of Dental Implants in Autogenous and Allogeneic Bone Blocks: A Systematic Review

Abstract: Background and Objectives: Preliminary studies emphasize the similar performance of autogenous bone blocks (AUBBs) and allogeneic bone blocks (ALBBs) in pre-implant surgery; however, most of these studies include limited subjects or hold a low level of evidence. The purpose of this review is to test the hypothesis of indifferent implant survival rates (ISRs) in AUBB and ALBB and determine the impact of various material-, surgery- and patient-related confounders and predictors. Materials and Methods: The nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 158 publications
1
9
0
Order By: Relevance
“…Several studies have reported that the success rates of the blocks are in the range of 94.7%-100% (Nissan et al, 2008;Barone et al, 2009;Carinci et al, 2010;Dahlin & Johansson, 2011;Pereira et al, 2015). A recent systematic review demonstrated that the implant survival rates in allogeneic bone blocks (96.23 ± 5.27%) were similar to those of ABBs (97.66 ± 2.68%) (Donkiewicz et al, 2021). A study conducted concerning bone gain and resorption using allogeneic bone blocks by Kloss et al (2018) reported a mean HBG of 5.2 ± 1.4 mm and a mean VBG of 0.2 ± 1.2 mm.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported that the success rates of the blocks are in the range of 94.7%-100% (Nissan et al, 2008;Barone et al, 2009;Carinci et al, 2010;Dahlin & Johansson, 2011;Pereira et al, 2015). A recent systematic review demonstrated that the implant survival rates in allogeneic bone blocks (96.23 ± 5.27%) were similar to those of ABBs (97.66 ± 2.68%) (Donkiewicz et al, 2021). A study conducted concerning bone gain and resorption using allogeneic bone blocks by Kloss et al (2018) reported a mean HBG of 5.2 ± 1.4 mm and a mean VBG of 0.2 ± 1.2 mm.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies suggested that the autologous jaw has good biocompatibility, bone conduction, bone induction, and high safety advantages in immediate implantation, but certain complications may be induced when the autologous jaw is used for bone extraction [ 11 , 12 ]. Patients who have allogeneic bone transplants, on the other hand, are more likely to develop a rejection reaction and infection [ 13 ]. The structure of nanohydroxyapatite (n-HA) is very similar to the crystal structure of the inorganic component of human bone, and it has good biological activity, no cytotoxicity, no immunogenicity, and good degradation performance [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, allogeneic bone grafts show a lesser risk of infections, postoperative morbidity, and unlimited bone availability. Although the clinical data shows excellent survival rates for allogeneic bone blocks ranging from 93.7 to 100.0%, the application of the allogeneic bone blocks is assumed to be more technique-sensitive [ 24 , 25 ]. Looking at the bone gain of allogeneic bone blocks, the literature provides several studies and meta-analysis with horizontal and vertical bone gains of 4.6±1.4 mm on average.…”
Section: Discussionmentioning
confidence: 99%